2020
DOI: 10.1007/s10596-020-09994-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation and calibration of coupled porous-medium and free-flow problems using pore-scale resolved models

Abstract: The correct choice of interface conditions and effective parameters for coupled macroscale free-flow and porous-medium models is crucial for a complete mathematical description of the problem under consideration and for accurate numerical simulation of applications. We consider single-fluid-phase systems described by the Stokes-Darcy model. Different sets of coupling conditions for this model are available. However, the choice of these conditions and effective model parameters is often arbitrary. We use large-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 51 publications
3
28
0
1
Order By: Relevance
“…In this case, the Beavers-Joseph condition (2.9) is suitable to couple the macroscale models. Rybak et al (2019) showed that this condition is also applicable when the flow is almost perpendicular to the interface. In this paper, we consider flow regimes with arbitrary flow directions (figures 1, 3 and 9) and we study different geometrical configurations for the porous-medium domain (figures 2 and 6).…”
Section: Model Validationmentioning
confidence: 98%
See 2 more Smart Citations
“…In this case, the Beavers-Joseph condition (2.9) is suitable to couple the macroscale models. Rybak et al (2019) showed that this condition is also applicable when the flow is almost perpendicular to the interface. In this paper, we consider flow regimes with arbitrary flow directions (figures 1, 3 and 9) and we study different geometrical configurations for the porous-medium domain (figures 2 and 6).…”
Section: Model Validationmentioning
confidence: 98%
“…To validate the applicability of the Beavers-Joseph interface condition (2.9) we evaluate cross-sections in the middle of the porous-medium domain at x 1 = 1.5 and also at x 1 = 2.2. For all simulations the fluid-porous interface Γ is located at x 2 = 0, directly on the top of the first row of solid inclusions as proposed in Lācis et al (2019) and Rybak et al (2019). The Beavers-Joseph parameter α BJ = 1 is commonly chosen in the literature.…”
Section: Staggered Circular Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…is based on obtaining the decomposition of the variation dJ 2 in the independent variations dm, dλ 1 , dλ 1 [25][26][27]. We decompose the variation in independent variations.…”
Section: Derivation Of Expressions For Functional Derivativesmentioning
confidence: 99%
“…Modeling one-phase flow in a coupled fluid-porous medium system has been the subject of active research since the pioneering work of Beavers and Joseph. 1,2 Applications of such a configuration are numerous, ranging from hydrology to chemical engineering. The main difficulty lies in a physically relevant way of reconciling a macroscopic description of the flow with a Darcy equation (or its variants) applicable in the bulk of the porous medium to the Navier-Stokes equation in the bulk fluid.…”
Section: Introductionmentioning
confidence: 99%